The Constitution and National Liberation - Lallana, Emmanuel (Kasarinlan: Philippine Journal of Third World Studies; Vol 2 No 2 (1986), 2007)
National liberation is socialism. A liberated Philippines is a socialist Philippines. The Constitutional Commission has not written a socialist constitution nor is the present government socialist. The progressive forces seem to be squandering a tremendous opportunity to transform society.